2020
DOI: 10.1186/s40663-020-00267-8
|View full text |Cite
|
Sign up to set email alerts
|

Selective logging enhances ecosystem multifunctionality via increase of functional diversity in a Pinus yunnanensis forest in Southwest China

Abstract: Background The impacts of selective logging on ecosystem multifunctionality (EMF) remain largely unexplored. In this study, we analyzed the response of nine variables related to four ecosystem functions (i.e. nutrient cycling, soil carbon stocks, decomposition, and wood production) to five selective logging intensities in a Pinus yunnanensis-dominated forest. We included a control group with no harvest to evaluate the potential shifts in EMF of the P. yunnanensis forests. We also assessed the relationship betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 77 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…We acknowledge that there are some limitations to this study, although our experimental unit is extensive compared with several other smaller selective logging experiments (Martin et al 2015, Huang et al 2020). According to the experience gained in previous studies, (BSRs) are affected by the spatial extent and grain size (Zhang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We acknowledge that there are some limitations to this study, although our experimental unit is extensive compared with several other smaller selective logging experiments (Martin et al 2015, Huang et al 2020). According to the experience gained in previous studies, (BSRs) are affected by the spatial extent and grain size (Zhang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…By removing a limited number of individual trees while leaving the rest intact, selective logging may change the composition and relative abundance of species, resulting in an increase or decrease in species diversity (Martin et al 2015, Geng et al 2021). As some individuals are removed leading to sparse stands, selective logging may change the original forest microclimate, soil moisture and nutrient status, and thus lead to changes in the processes affecting tree biology (Oldén et al 2019, Huang et al 2020). A growing number of studies have shown that high logging intensities may reduce biodiversity, disrupt forest structure, and impair the functioning of ecosystems (Asner et al 2004, Martin et al 2015, Huang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zavaleta et al [22] obtained in the study of testing the impact of species diversity on the function of grassland ecosystems that more diverse communities tend to consistently provide higher levels of multiple ecosystem functions over long periods of time. Traditional research in biodiversity and ecosystem functioning has primarily focused on the number and distribution of species as the primary metric for biodiversity measurement [23][24][25][26] . However, many studies have demonstrated that evolutionary history also plays a crucial role in influencing ecosystem functioning [16,23,27] .…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between biodiversity and ecosystem multifunctionality (BEMF) has become a new research hotspot in recent years. Species diversity is widely used in BEMF [ 1 , 2 , 3 , 4 , 5 , 6 ]. For example, Hector and Bagchi [ 7 ] quantitatively analyzed the impact of species diversity on EMF and concluded that maintaining higher EMF requires more species.…”
Section: Introductionmentioning
confidence: 99%